2003
DOI: 10.1074/jbc.m307286200
|View full text |Cite
|
Sign up to set email alerts
|

GPL, a Novel Cytokine Receptor Related to GP130 and Leukemia Inhibitory Factor Receptor

Abstract: We describe a novel cytokine receptor named GP130 Like receptor, or GPL, that displays similarities with the interleukin-6 and interleukin-12 family of signaling receptors. Four different isoforms diverging in their carboxyl terminus were isolated, corresponding to proteins encompassing 560, 610, 626, and 745 amino acids. Sequences included a signal peptide of 32 amino acids, followed by a cytokine binding domain containing four conserved cysteines, a WSDWS motif, and a region consisting of three fibronectin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
104
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(110 citation statements)
references
References 71 publications
2
104
2
1
Order By: Relevance
“…Recent studies from Zymogenetics researchers and from our group reported that OSMR also associate to a gp130-like receptor, GPL or IL-31R, to generate a functional receptor for IL-31 (32)(33)(34). In the present study we have shown that sOSMR together with GPL/IL-31R could also neutralize IL-31.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies from Zymogenetics researchers and from our group reported that OSMR also associate to a gp130-like receptor, GPL or IL-31R, to generate a functional receptor for IL-31 (32)(33)(34). In the present study we have shown that sOSMR together with GPL/IL-31R could also neutralize IL-31.…”
Section: Discussionmentioning
confidence: 99%
“…8B). Recent studies have demonstrated the OSMR involvement, together with Gp130-like receptor (GPL), also known as IL-31R, in the formation of a functional IL-31 receptor complex (32)(33)(34). We tested the possibility for sOSMR to also neutralize an IL-31 response in the T98G glioblastoma cell line (Fig.…”
Section: Soluble Osmr Tissue Distribution-tissue Distribution Was Anamentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokine and Cytokine Receptor Constructs-The proteincoding region for human IL-31 and the long form (745 amino acids) IL-31R␣ was identified in the genome data bank based on the published sequence (14,15). The IL-31 cDNA (encoding amino acid residues 24 -164, NCBI accession number NP001014358.1) was generated by reverse transcription-PCR using RNA from mitogen-activated human peripheral T-cells.…”
Section: Methodsmentioning
confidence: 99%
“…14) as a member of the IL-6R group that does not engage gp130, but OSMR␤, to form a signaling receptor complex (15,16). Based on the effects of ectopic expression in transgenic mice, IL-31, a CD4 ϩ T-cell-derived cytokine, has been associated with pruritis and dermatitis affecting dermal keratinocytes and dorsal root ganglia (17)(18)(19).…”
mentioning
confidence: 99%